Effect of Biopsychosocial Factors on Glycemic Control in Type 2 Diabetes Mellitus - Ozturk, Emel Olgun; Yakar, Burkay; Kaya, Mehmet Onur; Onalan, Erhan (Coll Physicians & Surgeons Pakistan, 2023)
Objective: To investigate the effect of diabetic patients' biopsychosocial factors on type 2 diabetes mellitus (T2DM) outcomes to contribute to diabetes mellitus management.Study Design: Cross-sectional descriptive study. Place and Duration of the Study: Department of Family Medicine, School of Medicine, Firat University, Turkey, from October 2021 to March 2022.Methodology: A total of 210 type 2 diabetic patients were included. The sociodemographic form, Beck depression inventory (BDI), multidimensional perceived social support scale (MSPSS), general self-efficacy scale (GES), and Diabetes self-care activities scale (DSCA) were used to assess the biopsychosocial factors. Controlled diabetes and uncontrolled diabetes classification was made according to HbA1c level (HbA1c cut-off value: <= 7%).Results: The median duration of T2DM (p=0.001), total cholesterol level (p=0.004) and fasting plasma glucose (p<0.001) were found to be higher in the uncontrolled diabetes group than in the controlled diabetes group. Spearman correlation test results showed a significant negative relationship between the scores of Beck depression and total cholesterol (r=-0.157, p = 0.023). There is a significant positive correlation between social support and total cholesterol (r=0.343, p<0.001), LDL (r=0.149, p= 0.031), trig-lyceride (r=0.165, p = 0.017), DSCA general diet score (r=0.367, p<0.001), DSCA physical activities (r=0.221, p = 0.001), DSCA glucose monitoring (r=0.302, p<0.001), DSCA foot care (r=0.311, p<0.001), and DSCA total scores (r=0.401, p<0.001).Conclusion: The present study showed that high BDI score was associated with low diabetes self-care score and presence of complications. Individuals' self-efficacy and high perception of social support were associated with increased diabetic self-care scores.
Keywords: Social support; Perception; Self care; Diabetes mellitus type 2; Diabetes complications; Depression